Computational Fluid Dynamics Analysis of Temperature Distribution in Solar Distillation Panel with Various Flat Plate Materials - Trismawati, Trismawati; Nanlohy, Hendry Y.; Riupassa, Helen; Marianingsih, Susi (Universitas Negeri Malang, 2024)
As the world population continues to grow, the demand for clean water is increasing daily, making it a crucial resource to access. However, there are ways to harness abundant resources like solar energy and seawater to produce clean water. The present studies have conducted experimental investigations to convert seawater into freshwater using solar stills, where solar energy is utilized as the primary heat source for evaporation. The temperature distribution inside the solar stills was analyzed using a flat plate made of three different materials: copper, stainless steel, and aluminum. To examine the temperature distribution and performance of the solar stills, researchers employed computational fluid dynamics simulations (Ansys R15.0). The results showed variations in temperature distribution among the three plate materials. Copper flat plates achieved the highest temperature, approximately 44.5 Celsius, followed by aluminum at 43.91 Celsius, while stainless steel exhibited the lowest temperature at around 42.01 Celsius. The average heat flux across the three materials was approximately 581 W/m2. Additionally, observations indicated that the amount of convection occurring in copper flat plates was 121.108 Watts; in aluminum, it was 118.517 Watts; and in stainless steel, it was 105.05 Watts. The radiation energy for stainless steel flat plates was 29.93 W; for copper, 16.14 W; and for aluminum, 13.49 W.